Canine guidance reconstruction with ceramic or composite resin: A 3D finite element analysis and in vitro wear study - Bueno, Mírian Galvão; Tribst, João Paulo Mendes; Borges, Alexandre Luiz Souto [UNESP] (Elsevier, 2022)
Statement of problem: Wear of the maxillary canine cusps is a common clinical condition which can affect function and esthetics and, in some situations, lead to occlusal pathology. The mechanical behavior of different restorative techniques for the condition is unclear. Purpose: The purpose of this in vitro study was to evaluate the biomechanical behavior of direct or indirect restorative techniques used in restoring canine guidance. Material and methods: Three-dimensional models obtained from 10 extracted undamaged maxillary canines were modeled by using reverse engineering. Each model received 2 different preparations: incisal (I) or incisal and labial (IL), restored with composite resin (CR) or ceramic (C), compared with unrestored teeth (U). Finite element analysis was used to evaluate the total deformation and the maximum principal stress. For the in vitro wear test, 30 teeth were divided into groups: U (control), I-CR, and IL-C. The teeth were wear tested for 240 000 cycles with a 2-mm sliding contact, a load of 49 N applied, with a 4-Hz cycle with a composite resin piston as antagonist. The wear of restorations and antagonists was quantified by the digital image correlation technique. The 1-way analysis of variance test for total deformation and the Tukey test for the maximum principal stress were used (α=.05) to statistically analyze the data. The Friedman test was applied in the comparison between wear cycles, and the Tukey test was used in the comparison among groups. Results: No significant difference was found among groups (P>.05) for the total deformation. IL-CR showed a higher failure probability, reaching stress peaks which exceeded the tensile strength of the material. I-CR showed greater wear in the in vitro test than IL-C (P=.02). No difference was found among groups in antagonist wear (P=.074). Conclusions: Ceramic restorations with labial involvement show biomechanical behavior closer to that of unrestored teeth in restoring canine guidance compared with composite resin.